DRIBBLING LEARNING MODEL ON SPORT GAMES FOR STUDENT SCHOOL STUDENT LEAGUE STUDENTS - Iqbal jasri; Firmansyah Dlis; Hidayat Humaid (Journal Physical Education, Health and Recreation, 2018)
The goal to be achieved from this research and development is to produce dribbling learning model product on football game for junior high school students. This research and development is conducted to be able to obtain information about the development and application of dribbling learning model on the game of football for junior high school students and to know the effectiveness of the resulting model. This research uses Research & Development (R & D) method from Borg and Gall. Subjects in this study were junior high school students consisting of 40 students. The steps in this study are: needs analysis, expert evaluation (initial product evaluation), small group trial, and field testing. Test the effectiveness of the model using soccer dribbling skills test used to determine the level of dribbling ability of students before and after giving treatment dribbling learning model developed. Initial test done obtained level of dribbling ability of student is 3,236 second. After given treatment dribbling learning model obtained level of dribbling ability students 9.736 seconds. On the significant test the difference with spss 16 obtained mean = -6.500 shows the difference of pre-test results and post-test results, t-count = -28.429 df = 37 and p-value = 0.00 <0.05 which means there is a significant difference between before and after given the treatment of dribbling learning model on the game of football. Thus a dribbling learning model on football games for junior high school students is effective to improve dribbling skills in football games for Junior High School Students.